A competência do município para legislar sobre interesse local: um estudo de caso do município de Rio Verde na limitação do plantio de cana em seu território - Schüz Araújo, Hebert Mendes de (2014)
This research aims to analyze the limitation of planting cane sugar Rio Verde from the perspective of local interest and the advancement of the sugarcane sector driven by the expansion of the agricultural frontier process. Therefore, the approach examines the ramifications of Complementary Law No. 5.200/2006 with the declaration of unconstitutionality of Article 1 thereof , as well as the municipal competence, in order to understand the reason of legislative and legal disputes involving Federal, State and Municipalities in the context of agrarian and environmental issue . Thus , the aim is to raise the debate about the social function of property , federalism , municipal autonomy , and the blurring of boundaries of competence in editing standards by federal entities . From there , the research will conclude by the need to understand local interest , according to the environment protection and preservation of the economic development of the municipality of Rio Verde style. Finally , it will be evident that there is no invasion of legislative powers when the municipality acts in obedience to local interest and it will prevail in society.